Big Shoes to Fill: How Star Search Behavior and Network Structure Influence Coinventor Mobility and Innovation Performance upon Star Exit - Awate, Kiran S.; Khanna, Rajat; Srikanth, Kannan (Organization Science, 2025)
A robust body of literature examines how star inventors influence their firms’ innovation trajectories, but how their departure affects firm innovation outcomes is imprecisely understood. Star departure has two kinds of spillover effects on firms: increased coinventor mobility and reduced coinventor performance. In this study, we aim to understand whether and why these spillover effects may systematically differ between stars. We argue that star search behavior influences the nature of embeddedness—positional and structural—in the star-coinventor network, which in turn differentially affects the two spillover effects arising from star exit. We test our hypotheses using patent data from 1985 to 2010 in the pharmaceutical industry. We find that when compared with the exit of an average star inventor, the exit of a broad-searcher star inventor is associated with a greater reduction in coinventor performance but not in coinventor mobility. In contrast, the exit of a deep-searcher star inventor is associated with an increase in coinventor mobility but has a smaller effect in reducing (remaining) coinventor performance than the departure of a broad-searcher star. We find that variation in the star’s collaboration network structure underlies these effects. Further, network structure has countervailing effects on coinventors’ mobility and (remaining) coinventors’ performance. This study helps better understand the human capital versus relational capital effects of inventor mobility. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2020.14415 .